Interior Design with The Bali Village Nuances At Facility Area in The Ubud Village Resort - Aiko Ishii; Adi Wardoyo (Jurnal Sains dan Seni ITS, 2016)
Along with the modernization, many works of region cultural were forgotten but improve and innovate the technology especially in the design and buildings construction. Characteristic of Balinese buildings has changes since before and after the influence of Majapahit Hinduism came to Bali. The building character before the influence was mostly built by bamboos. Bamboo building in Bali can be seen in various places such as facilities areas like resort. Departing from the name of the resort is The Ubud Village Resort, the writer will optimize the interior in the resort facility area with the concept of "Kampung Bali". The design is expected to take advantage of innovations in a more modern while still preserving the culture of Bali. The Concept that were presented at this resort is to describe a village in Bali during the traditional era with the natural impression, but more dynamic and add some innovations to the art of Balinese building in order to face a period of modernization.